2023
DOI: 10.1136/bmjopen-2023-075172
|View full text |Cite
|
Sign up to set email alerts
|

Patient randomised controlled trial of technology enabled strategies to promote treatment adherence in liver transplantation: rationale and design of the TEST trial

Marina Serper,
Alexander Burdzy,
Douglas E Schaubel
et al.

Abstract: Background and aimsLiver transplantation is a life-saving procedure for end-stage liver disease. However, post-transplant medication regimens are complex and non-adherence is common. Post-transplant medication non-adherence is associated with graft rejection, which can have long-term adverse consequences. Transplant centres are equipped with clinical staff that monitor patients post-transplant; however, digital health tools and proactive immunosuppression adherence monitoring has potential to improve outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…[8] While studies have demonstrated promise in the use of digital tools to manage cirrhosis, it is essential to determine the feasibility and effectiveness of a comprehensive cirrhosis-specific RPM before widespread implementation of this technology. [9][10][11] In this project, we aimed to: (1) design and implement a cirrhosis-specific RPM (CiRPM) program, as well as (2) show its utility through measurement of potential clinical benefit, patient satisfaction, and patient adherence. We hope this can serve as a roadmap for other personalized remote monitoring programs for patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] While studies have demonstrated promise in the use of digital tools to manage cirrhosis, it is essential to determine the feasibility and effectiveness of a comprehensive cirrhosis-specific RPM before widespread implementation of this technology. [9][10][11] In this project, we aimed to: (1) design and implement a cirrhosis-specific RPM (CiRPM) program, as well as (2) show its utility through measurement of potential clinical benefit, patient satisfaction, and patient adherence. We hope this can serve as a roadmap for other personalized remote monitoring programs for patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…RPM is becoming increasingly popular, and its use will likely continue to increase in the near future due to recent changes in Medicare establishing a billing code for RPM 8 . While studies have demonstrated promise in the use of digital tools to manage cirrhosis, it is essential to determine the feasibility and effectiveness of a comprehensive cirrhosis-specific RPM before widespread implementation of this technology 9–11 . In this project, we aimed to: (1) design and implement a cirrhosis-specific RPM (CiRPM) program, as well as (2) show its utility through measurement of potential clinical benefit, patient satisfaction, and patient adherence.…”
Section: Introductionmentioning
confidence: 99%